1988
DOI: 10.1172/jci113569
|View full text |Cite
|
Sign up to set email alerts
|

Increase of the 40,000-mol wt pertussis toxin substrate (G protein) in the failing human heart.

Abstract: Human heart failure is associated with a diminished contractile response to 0-adrenergic agonists. We hypothesized that alterations in the activity of a guanine nucleotide-binding regulatory protein (G protein) might be partially responsible for this abnormality. We therefore measured the activity of G proteins in failing human myocardium utilizing bacterial toxin-catalyzed ADP ribosylation. The activity of a 40,000-mol wt pertussis toxin substrate (aG40) was increased by 36% in failing human hearts when compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
169
2
5

Year Published

1990
1990
2009
2009

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 523 publications
(190 citation statements)
references
References 47 publications
14
169
2
5
Order By: Relevance
“…Previous studies have shown that muscarinic receptor density in myocardium from patients with end-stage heart failure is unchanged as compared to receptor density in normal myocardium (13)(14)(15), but that G i activity is increased (15)(16)(17). The results of the present study provide insight into the function of muscarinic pathways in the setting of human congestive heart failure.…”
Section: Discussionsupporting
confidence: 48%
See 4 more Smart Citations
“…Previous studies have shown that muscarinic receptor density in myocardium from patients with end-stage heart failure is unchanged as compared to receptor density in normal myocardium (13)(14)(15), but that G i activity is increased (15)(16)(17). The results of the present study provide insight into the function of muscarinic pathways in the setting of human congestive heart failure.…”
Section: Discussionsupporting
confidence: 48%
“…Muscarinic stimulation may have activated the inhibitory G protein, G i , leading to reduced adenylate cyclase production of cAMP (25). This may be relevant in the setting of heart failure, where G i activity is increased (5,(15)(16)(17)(18). The effects of acetylcholine may have been secondary to stimulation of inhibitory muscarinic receptors on adrenergic nerve terminals (6,26).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations